What should we conserve? Farmer narratives on biodiversity values in the McLaren Vale, South Australia. (April 2019) - Bardsley, Douglas K.; Palazzo, Elisa; Stringer, Randy
Abstract: Major challenges are emerging to integrate private lands into whole-of-landscape conservation policy, especially if definitions of biodiversity and conceptions of conservation alienate farming communities. Insufficient attention has been paid to the way that farmers perceive and value biodiversity. By undertaking 'walk-and-talk' in-depth interviews with leading farmers in the South Australian viticultural region of the McLaren Vale, seven important narratives were identified on the way that farmers conceive of and exploit biodiversity on-farm. Farmers' conceptions of biodiversity challenge traditional policy divisions between 'natural' and anthropogenic biodiversity and represent a sophisticated understanding of agricultural and regional ecology. While farmers clearly recognise and prioritise important biodiversity values, the dominant policy frameworks are not effectively defining, quantifying or supporting that biodiversity which is constantly being regenerated through farming practices. A range of opportunities for better conservation emerge from a recognition that productive farming activities and associated agricultural biodiversity form a vital part of the region's biocultural heritage. Of particular importance is the need for farmer definitions of biodiversity to be included in policy both to guide new connections between private landowners and biodiversity conservation, and to normalise goals of sustainable environmental management across rural landscapes.